Developing Students as Advocates through a Pilot Advocacy Curricular Thread within a PharmD Curriculum - Cortney M Mospan; McKenzie Calhoun (University of Minnesota Libraries Publishing, 2016)
There is a need for education about and development of advocacy skills within student pharmacists. Pharmacy literature describes experiences incorporating advocacy education within curricula; however, these are often singular, limited experiences. To increase student pharmacists' awareness, knowledge, and skills, effective advocacy curricular threads are necessary within curricula. This paper provides rationale for the need for a greater emphasis on development of these skills within student pharmacists, evidence of curricular experiences surrounding advocacy from the literature, initial observations from a piloted curricular thread at one school, and implications for the academy. Conflict of Interest Dr. Calhoun is a Board member of the Tennessee Pharmacists Association.   Type: Idea Paper